Integration of membrane technology into hydrogen production plants with CO2 capture: An economic performance assessment study. (November 2015) - Ma, Liang-Chih; Castro-Dominguez, Bernardo; Kazantzis, Nikolaos K.; Ma, Yi Hua
Highlights: Economic performance assessment framework for hydrogen production with integrated membrane technology. Market and regulatory uncertainties are explicitly recognized. Comparative economic assessment against competing technology options. Effect of future CO2 emissions regulations on plant's economic performance. Detailed Monte Carlo simulation studies in the presence of uncertainty. Abstract: An economic performance evaluation framework for hydrogen production (HP) plants with integrated catalytic membrane reactor (CMR) modules is presented (HP-CMR) in light of their enhanced environmental performance prospects. A detailed comprehensive net present value (NPV) model is first developed in order to assess the economic viability of HP-CMR plants, while irreducible sources of market and regulatory uncertainty are identified and their effect on the plant's economic performance is explicitly taken into account through Monte-Carlo techniques. As a result, the proposed economic performance evaluation framework for an HP-CMR plant allows the derivation of distribution profiles of economic performance outcomes rather than single-point value estimates that often lead to unsatisfactory valuation assessments by overlooking significant uncertainty effects over the plant's lifetime. Within the above framework, the HP-CMR plant is comparatively assessed against the conventional HP plant with and without carbon capture and sequestration (CCS) systems. It is shown that future regulatory action on CO2 emissions leads to comparatively appealing distribution profiles of economic performance outcomes for HP-CMR plants in the presence of uncertainty, thus offering a window of opportunity for this new technology option to emerge as a viable one for hydrogen production in a carbon-constrained world. Finally, the provision of a set of incentives is considered that could potentially facilitate the demonstration stage of the HP-CMR technology option on the commercial scale.